The Influence of Location, Price Perception, and House Design on The Purchase Intention of Mansion Nine Landing Houses - Pratama, Reyhan Atallah Syah; Rohman, Fatchur (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose – This study aims to analyze the effects of location, price perception, and house design on the purchase intention of Mansion Nine landed houses among millennials in Surabaya.  Design/methodology/approach – This study employs a quantitative explanatory research design to examine the relationships between location, price perception, house design, and purchase intention. Data were collected through an online questionnaire from 220 millennial respondents who are familiar with Mansion Nine housing products. The data were analyzed using multiple linear regression with IBM SPSS Statistics version 26.   Findings – The results indicate that location, price perception, and house design each have a positive and significant effect on purchase intention. These findings suggest that strategic location, competitive pricing, and attractive housing design are key factors influencing millennials’ intention to purchase landed houses.   Originality/value – This study contributes to real estate marketing literature by identifying the combined influence of location, price perception, and house design on millennial purchase intention in the Indonesian housing sector. The findings provide practical implications for property developers in designing more effective marketing strategies that align with millennial preferences.